Victimology: a comprehensive approach to forensic, psychosocial and legal perspectives - Gopalan, Rejani Thudalikunnil (Springer, 2022)
1.Recent updates on victimology and its influence on Criminal Justice System -- 2. Working with victims : Psychological assessment of victims and mental health of professionals -- 3. Sexual abuse: Victims and perpetrator -- 4 . Adult molested as child -- 5.Intimate partner violence and victims -- 6. Child maltreatment -- 7. Cyber Victimization -- 8. Victims of war and terrorism -- 9. Victims of natural calamities -- 10.Victimization at school and work place -- 11.Human Trafficking -- 12.Crimes against person -- 13. Crimes against Property -- 14. Elder abuse, Victims with disabilities -- 15. Consequences of victimization, survivorology, and bystanderology -- 16. Re-victimization -- 17. Early Childhood Violence Exposure and Subsequent Antisocial Behavior: Canadian Indigenous Young offenders Case Study -- 18. Understanding Adolescent Behavior and Victimization of Special Populations Through Bronfenbrenner’s Bioecological Theory -- 19. Forensic investigations and victims -- 20. Medical and psychological management of victimization.